2015
DOI: 10.1016/j.wear.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A computational approach to fretting wear prediction at the head–stem taper junction of total hip replacements

Abstract: Wear is one of the main reasons for failure of modular total hip replacements. Recent evidence suggests that fretting wear occurs at the taper junction which provides fixation between the prosthesis femoral head and stem components. The fine metallic wear debris that is released can lead to adverse soft-tissue reactions which can necessitate a revision surgery. The present study proposes a computational methodology utilising an energy wear law and a 3D finite element model to predict fretting wear at the taper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…A study on the effect of β on the calculation of wear undertaken in the previous study has demonstrated that β =10 5 provides converged results (English et al, 2015). However, in this study, by employing a new model with a more realistic boundary condition and a refined mesh at the contact area, the β value has been converged at 250,000 load cycles, which further reduced the computational wear analysis time.…”
Section: Implementation Of the Wear Lawmentioning
confidence: 84%
See 4 more Smart Citations
“…A study on the effect of β on the calculation of wear undertaken in the previous study has demonstrated that β =10 5 provides converged results (English et al, 2015). However, in this study, by employing a new model with a more realistic boundary condition and a refined mesh at the contact area, the β value has been converged at 250,000 load cycles, which further reduced the computational wear analysis time.…”
Section: Implementation Of the Wear Lawmentioning
confidence: 84%
“…This law considers the interfacial shear work and relative motion as predominant parameters to calculate the volumetric wear. Its implementation in finite element analysis has been explained previously (English et al, 2015). Briefly, according to the "Dissipated Energy" wear law, the cyclic wear depth (W c ) for a single cycle of loading can be presented using Equation 1,…”
Section: Implementation Of the Wear Lawmentioning
confidence: 99%
See 3 more Smart Citations